From prescription patterns to drug safety: a closer look at non-steroidal anti-inflammatory drugs and analgesics in outpatient pharmacy - Saeed, Zainab Mohamed; Sridhar, Sathvik B.; Shareef, Javedh; Rashed Alsereidi, Amal Mohamed (Frontiers in Pharmacology, 2025)
IntroductionNon-steroidal anti-inflammatory medicines (NSAIDs) help to lower inflammation and pain, but improper prescription can cause potential drug-drug interactions (pDDIs), affecting the therapeutic outcomes. Given the great frequency of polypharmacy and concomitant medication interactions, NSAID-related problems are especially pertinent in outpatient settings. This study aims to assess the prescription pattern of NSAIDs at the Outpatient Pharmacy Department of a Secondary Care Hospital in the Northern Emirates of the United Arab Emirates.MethodsA prospective observational study based on data from electronic medical records of patients who received NSAID prescriptions from Jan–June 2023. Data collected were screened for prescription patterns of NSAIDs and polypharmacy, and the potential drug-drug interactions (pDDIs) were identified using the Portable Emergency Physician Information Database (PEPID). Data were extracted and analyzed using descriptive statistics and logistic regression analysis to study the association between treatment-related variables and the presence of pDDIs. Chi-square was used to test the association between the type of NSAID prescribed and co-prescribed gastro-protective agents. P < 0.05 was considered statistically significant.ResultsIn total, 1005 NSAID prescriptions were analyzed, with a majority (53.23%) being prescribed to female patients. Pain related to elbow/shoulder/joints/lower back (41.09%) was the most common diagnosis in the study populations. Celecoxib (49.7%) was the most commonly prescribed oral, and Ketoprofen (39.5%) was the predominant topical NSAID. A significant association was found between the prescribed NSAID and its co-prescription with gastroprotective agents, specifically ibuprofen, celecoxib, piroxicam, meloxicam (P < 0.001), diclofenac (P = 0.007), and aspirin (P = 0.001). Age and chronic illnesses such as diabetes mellitus (OR = 1.446; 95% CI: 1.018–2.054) and cardiovascular disease (OR = 1.818; 95% CI: 1.279–2.585) are significantly associated with polypharmacy. Multiple logistic regression analysis revealed that the pDDIs were significantly higher with an increasing number of prescribed drugs and co-morbidities (p < 0.001).ConclusionThe study examines NSAID prescribing trends and emphasizes the potential for drug-related issues, particularly in light of polypharmacy, which calls for careful monitoring and prescribing practices. Healthcare providers should routinely conduct medication reviews and team up with clinical pharmacists to ensure rational NSAID use, reduce drug interactions, and enhance patient safety by thus mitigating this risks.